Peran guru dalam menanamkan akhlak mulia di Era digital - Ivanda, Salsa Bila; Neni, Neni (Jurnal Pendidikan Agama Islam, 2025)
The role of teachers in instilling noble character in the digital age is an important aspect in shaping the character of students amid rapid technological developments. This study aims to describe how teachers play a role in instilling moral and spiritual values in an educational environment that has been influenced by digital advances. The method used is a descriptive qualitative approach with a literature study technique that refers to various sources such as journals, books, and current scientific articles. The results of the study show that teachers have a central role as role models, mentors, and guides so that students are able to use technology positively. Teachers are also expected to be able to integrate moral values through character-based learning, the use of educational digital media, and collaboration with parents in supervising their children's morals. These findings confirm that the effectiveness of instilling noble character is greatly influenced by teachers' ability to balance technological aspects with ethical and spiritual values. Therefore, teachers play a role not only as educators but also as moral role models who shape the character of the digital generation.